Evaluasi Sistem Pengelolaan Persampahan di Perkotaan Amurang - Indra Effendhi; Papia Franklin (Sabua : Jurnal Lingkungan Binaan dan Arsitektur, 2021)
Indonesia is a developing country with a very high population. One of the problems in Indonesia is the problem of waste, waste is an item that is no longer used and thrown away. The development of a city area cannot be separated from the lifestyle of the urban community with changes in the level of consumption becoming more instantaneous, the pattern of life and the level of public awareness which plays an important role as a producer of waste. Amurang City has a solid waste management system that is managed by the local government which is implemented by the Environmental Agency, technical support facilities for solid waste management operations are quite good, at some points of the road you can find landfills (TPS) of varying sizes. Other facilities, such as the integrated garbage dump (TPST), are still very minimal, because the 3R waste concept has not been implemented. This study aims to identify and evaluate the waste management system in the Amurang Urban Area (Amurang & West Amurang Districts) by applying qualitative methods and descriptive methods. From the results of the research, the researchers concluded that the waste management in Amurang Urban area has been going well, leading to Government Regulation No. 3 of 2014 concerning regional spatial planning.Keywords:Evaluation, Waste, Amurang City